A multicenter phase 2 study of pomalidomide plus dexamethasone in patients with relapsed and refractory multiple myeloma: the Japanese MM-011 trial. Issue 1 (December 2015) - Ichinohe, Tatsuo; Kuroda, Yoshiaki; Okamoto, Shinichiro; Matsue, Kosei; Iida, Shinsuke; Sunami, Kazutaka; Komeno, Takuya; Suzuki, Kenshi; Ando, Kiyoshi; Taniwaki, Masafumi; Tobinai, Kensei; Chou, Takaaki; et al.
Abstract Background The immunomodulatory agent pomalidomide in combination with low-dose dexamethasone has demonstrated efficacy and safety for the treatment of relapsed and refractory multiple myeloma (RRMM) in phase 2 and 3 trials. However, these trials enrolled very few Asian patients. Methods This phase 2 study investigated pomalidomide plus low-dose dexamethasone in 36 Japanese patients with RRMM after ≥2 prior therapies. Results Patients enrolled in the study had a relatively high disease burden (81 % Durie–Salmon stage II or III) and were heavily pretreated (median, 6.5 prior antimyeloma regimens). The overall response rate was 42 % (1 patient with complete response and 14 with partial response), with an additional 44 % (16 patients) achieving stable disease (SD). Response rates in patients aged ≤65 years and >65 years were 47 and 35 %, respectively. None of the five patients with extramedullary disease achieved a response, with three of them maintaining SD of short duration. Median progression-free survival was 10.1 months after a 7.7-month median follow-up, and the median overall survival was not reached. The most frequent grade ≥3 adverse events (AEs) were neutropenia (64 %), anemia (42 %), and thrombocytopenia (31 %). The most frequent nonhematologic grade ≥3 AEs were pneumonia and decreased appetite (8 % each). Adverse events in patients aged >65 years were similar to those in patients aged ≤65 years, except for a higher rate of grade ≥3 pneumonia. Conclusions Collectively, the results of this study demonstrate that pomalidomide plus low-dose dexamethasone is an effective and safe treatment for Japanese patients with RRMM, although careful attention needs to be paid to serious infections. Trial registration: Clinicaltrials.gov NCT02011113